Bi2O3 modification of HZSM-5 for methanol-to-propylene conversion: evidence of olefin-based cycle. Issue 27 (15th March 2017) - Zhang, Hairong; Ning, Zhangxuan; Liu, Hongyan; Shang, Jianpeng; Han, Shenghua; Jiang, Dingding; Jiang, Yu; Guo, Yong
Abstract : Bi2 O3 -modified HZSM-5 catalysts were prepared via a traditional wetness impregnation approach, and used for the methanol-to-propylene conversion reaction. Abstract : Bi2 O3 -modified HZSM-5 catalysts were prepared via a traditional wetness impregnation approach, and used for the methanol-to-propylene conversion reaction. The selectivity for propylene increases significantly with bismuth loading, while that for ethylene shows the opposite trend. However, the Bi2 O3 /HZSM-5 catalysts have significantly lower capacities for methanol conversion than the parent HZSM-5. The underlying causes are the reduced acid site strength, narrower pore openings, and reduced pore width in Bi2 O3 /HZSM-5. This work provides insights into the olefin-based cycle operation for methanol-to-olefin reactions using modified HZSM-5 catalysts.